The Arctic Ocean Eigen Oscillations - Proshutinsky, A. Yu.; Polyakov, I. V. (1992)
The spectral task on the eigen oscillations of the Arctic Ocean level was solved using numerical integration of tidal Laplace equations without friction as the non-stationary boundary-value problem. The adiabatic conditions were prescribed at the boundaries. Free oscillations were induced by an arbitrary initial perturbation in the level field. The spectra of fire oscillations of the Arctic Ocean have significant maxima of spectral density at the periods of 30.38, 23.70, 17.30, 13.91, 12.55, 11.03, and 8. 10 hours. The zoning of the Arctic Ocean was made on the basis of differences in the spectra of free oscillations in some of its areas, the results of zoning being consistent with common representations of the geographical subdivision of the Arctic Ocean into basins, seas, and bays. The possibility of resonance amplification of shelf waves and double Kelvin waves in the areas with significant bottom topography irregularities was revealed. The resonance nature of the surge level oscillations caused by rapidly shifting cyclones was proven. The experimental studies confined the hypothesis of the resonance mechanism of tidal motions in the marginal seas of the Arctic Ocean. This article is from 'Proceedings of the International Conference on the Role of the Polar Regions in Global Change Held in Fairbanks, Alaska on 11-15 June 990. Volume 1', AD-A253 027, p347-354. See also Volume 2, AD-A253 028.